Parenting Program Implementation to Increase Positive Parenting Behavior - Erick Maison Putra; Reggy Ariska Firdhayani (CERDAS - Jurnal Pendidikan, 2023)
This research is motivated by the problem of the lack of positive parenting knowledge from every parent at Tulip Early Childhood Education. Every parent has a different parenting background but has the same parenting problems by having positive goals. This happens because of the lack of knowledge that every parent in PAUD has in educating children who aim towards positive parenting. This study used a descriptive qualitative approach, with interview and observation techniques. The subjects in this study were five people, namely three parenting participants, one PAUD manager, and one resource person. The results of the study show that: 1) the process of implementing the parenting program involves the presence of parents in parenting activities so that they always follow the material presented, such as skills, spiritual teachings, cooking, and so on. 2) The attitude of parents after participating in the parenting program shows positive parenting behavior. 3) The inhibiting factor of parenting program behavior is in the form of economic difficulties, and the main factor that is felt to be hindering is the presence of parents and children who still need time to adapt in applying positive things in everyday life, and there are still many parents who cannot attend or arrive late so that not all information can be conveyed by the speaker. While the supporting factors are in the form of the arrangement of committee activities, positive responses from parents, and facilities and infrastructure that support the smooth running of these parenting activities. In addition, there is cooperation with posyandu partners, BKB, puskesmas, experts in the field of education. Suggestions for parents parents should be firm when educating and caring for children so that children get used to the application of positive parenting.